Jobs, Institutions, and Beneficial Retirement. (22nd August 2013) - Lang, Gerald
Abstract According to Saul Smilansky's 'Paradox of Beneficial Retirement', many serving members of professions may have decisive integrity‐based reasons for retiring immediately. The Paradox of Beneficial Retirement holds that a below‐par performance in one's job does not require any outright incompetence, but may take a purely relational form, in which a good performance is not good enough if it would be improved upon by someone else who would be appointed instead. It is argued, in response, that jobs in the sectors Smilansky mentions are not merely positions to optimize the goals of the profession, but are professional careers in which there is the possibility of security and personal fulfilment. The article also explores connections between Smilansky's argument and G. A. Cohen's anti‐incentives argument against Rawls. It is suggested that both thinkers underappreciate the relationship between personal reasons and institutional reasons.1